Kinetic Isotope Effects on the AroA Reaction: A Mechanistic Investigation of the AroA Reaction - Dhekney, Girija (My University, 2004)
AroA catalyzes the synthesis of enolpyruvyl shikimate 3-phosphate (EPSP) from phosphoenolpyruvate (PEP) and shikimate 3-phosphate (S3P). It is part of the shikimate pathway which produces most aromatic compounds in plants, bacteria, and apicomplexa. The shikimate pathway is missing in mammals making AroA a potential antimicrobial target. It catalyzes a two step mechanism where the hydroxyl group of S3P adds across the double bond of PEP to form a tetrahedral intermediate (THI). Elimination of phosphate from the THI completes the reaction. In this study, kinetic isotope effects (KIEs) on the enzymatic reaction, as well as the non-enzymatic acid-catalyzed breakdown of PEP, were measured. A method for measuring KIEs by whole molecule mass spectrometry was developed. KIEs were determined using isotopologues of PEP. The KIEs measured on the enzymatic reaction using [3,3-2H2]pEP was 0.985 ±0.003 and [3-13C]PEP was 0.97 ± 0.01. The KIE measured on the non-enzymatic reaction using [3,3-2H2]PEP was 1.180 ± 0.009. Acid-catalyzed PEP breakdown proceeds through protonation at C3 to form an oxocarbenium ion intermediate. This is proposed to mimic the first step in the AroA-catalyzed reaction of S3P to PEP.
Keywords: Biochemistry; Biochemistry